Kualitas papan partikel dari limbah serat kelapa muda dan styrofoam untuk kebutuhan dunia industri - Markus Nanda Andika; Enda Apriani; Syaiful Mansyur; Sumpena Sumpena (Jurnal Engine: Energi, Manufaktur, dan Material, 2022)
Waste of young coconut fiber can potentially be used as reinforcement for new particleboard material. This potential agricultural waste is quite large in Indonesia. Styrofoam waste is also a problem to date. This is because the use of styrofoam as a food wrapper is still quite high in Indonesia. Besides being environmentally friendly, this particleboard also has economic value in the industrial world. Young coconut waste is crushed with a coconut fiber decomposing machine. Styrofoam as an adhesive is dissolved with gasoline. Each proportion of raw material for young coconut fiber: styrofoam, which is 25: 75 (%), 50: 50 (%), and 75: 25 (%).The test results of the mechanical properties of the particleboard with Composition III showed better results than the particleboard with Composition I and Composition II, which obtained an average MoE value of 832.69 kgf / cm2, an average MoR value of 12.10 kgf / cm2, and the average IB value of 2.01 kgf / cm2.